Postharvest process, marketing, and competiveness of domestic rice - Johnson, Michael E.; Ajibola, Akeem (University of Pennsylvania Press, 2016)
The purpose of this chapter is to review the postharvest processing and marketing activities of domestic rice production in Nigeria in order to evaluate domestic production's ability to compete with imports. This is accomplished by assessing the structure, conduct, and performance of the domestic rice sector. In doing so, key challenges and opportunities facing the sector are highlighted and research questions raised to address them, such as these: Is there potential to improve the quality and competitiveness of the final local rice product in domestic markets? Are there differential abilities and efficiencies among existing mill types (small to large) that affect their capacity to supply the domestic market? Are there lessons that can be drawn from elsewhere in West Africa and Asia? The chapter has been organized with this logical sequence of evaluation in mind.